The 4C Learning Innovation as an Effort to Improve Teacher's Professionalism and Students' Competency at Private Vocational High School of Walisongo 2 Gempol, Indonesia - Afifudin, Afifudin (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2022)
This research was conducted to observe the efforts of a private school to improve teachers’ professionalism and students’ competency. This study used a case study model with a descriptive qualitative approach. Here, data collection was done through in-depth interviews, observation, and document study. The results showed that teachers with knowledge and motivation improve their service to students through teaching skills. Teachers’ knowledge was a learning innovation to the better learning process. They had the 4C skills: critical and creative thinking, collaboration, communication, and creativity. Teachers’ professionality then affected students’ competency, be it soft and hard skills. However, the evidence that was found at Private Vocational High School of Walisongo 2 Gempol, Indonesia could not be generalized to all private vocational high schools. Thus, further research on other private schools in Indonesia is needed to develop creativity and innovation to support graduates’ quality